ANFO vapour detection with conducting polymer percolation network sensors and GC/MS. Issue 7 (15th February 2021) - Lefferts, Merel J.; Humphreys, Lisa H.; Mai, Nathalie; Murugappan, Krishnan; Armitage, Ben I.; Pons, Jean-François; Castell, Martin R.
Abstract : Ammonium nitrate mixed with fuel oil (ANFO) is commonly used in improvised explosive devices (IEDs). Abstract : Ammonium nitrate mixed with fuel oil (ANFO) is commonly used in improvised explosive devices (IEDs). The development of ANFO vapour sensors that are small, inexpensive, and easy to use will enable widespread IED detection in the context of security and humanitarian demining. Because of concealment and the low vapour pressures of most explosive materials, achieving sufficiently high sensitivity and low limits of detection are some of the main challenges of explosives vapour detection. Here ANFO chemiresistive vapour sensors based on polypyrrole (PPy) percolation networks are presented and compared to gas chromatography-mass spectroscopy (GC/MS) results for ANFO. Improved sensitivities are achieved by using a polymer percolation network instead of a thin film for the gas sensors. Vapour concentrations are detected of 13–180 ppb of ammonia emitted by a variety of different ammonium nitrate-containing fertilisers and fertiliser-diesel mixtures.